Health and Disease Are Dynamic Complex-Adaptive States Implications for Practice and Research - Sturmberg, Joachim P. (Frontiers in Psychiatry, 2021)
People describe their health along an experiential continuum, from excellent, very good, good, fair to poor. A person’s experience of health can be surprising to the observer – some are in good health with disabling disease, others are in poor health without the evidence of any. Health experiences are nonlinear, i.e. a given increase in disease burden can be associated with an unpredictable and disproportionate loss in health. Health experiences – as phenomenological events – create patterns. Two questions arise: how do we understand the formation of these patterns, and how can we help people to swab undesirable patterns for more desirable ones? This paper firstly reviews the dynamic nature of the health experiences, and secondly describes health patterns as emergent outcomes of physiological dynamics of a complex adaptive system that is on the one hand bounded by a person’s external environment and biological blueprint, and on the other regulated by HPA-axis pathways and their feedback loops. These considerations lead to a different – new paradigm – question: What in this patient’s life are the key triggers of HPA-axis dysregulation resulting in dis-ease and disease, and what are the consequences of disease and dis-ease on the person as a whole? The final section suggests ways of translating these expanded understandings to clinical practice and future research endeavours.